The Relationship Between Plasma Tetrahydrocannabinol Levels and Intraocular Pressure in Healthy Adult Subjects - Mosaed, Sameh; Smith, Andrew K.; Liu, John H. K.; Minckler, Donald S.; Fitzgerald, Robert L.; Grelotti, David; Sones, Emily; Weinreb, Robert N.; Marcotte, Thomas D. (Frontiers in Medicine, 2022)
Background: Δ9-tetrahydrocannabinol (THC) has been shown to decreased intraocular pressure (IOP). This project aims to define the relationship between plasma THC levels and IOP in healthy adult subjects. Methods: 11 healthy subjects received a single dose of inhaled cannabis that was self-administered in negative pressure rooms. Measurements of IOP and plasma THC levels were taken at baseline and every 30 minutes for 1 hour and afterwards every hour for four hours. IOP reduction and percent change in IOP over time were calculated. Linear regression models were used to measure the relationship between IOP and plasma THC levels. Two line linear regression models with F-tests were used to detect change points in the regression. Then, Pearson correlations were computed based on the change point. Results: 22 eyes met inclusion criteria. The average peak percentage decrease in IOP was 16% at 60 minutes. Percent IOP reduction as well as total IOP reduction demonstrated a negative correlation with THC plasma levels showing r-values of -0.81 and -0.70 respectively. F-tests revealed a change point in the regression for plasma levels greater than 20 ng/ml. For levels greater than 20 ng/ml, the correlation coefficients changed significantly with r-values of 0.21 and 0.29 (p-value <.01). Conclusion: Plasma THC levels are significantly correlated with IOP reduction up to plasma levels of 20 ng/ml. Plasma levels greater than 20 ng/ml were not correlated with further decrease in IOP. More research is needed to determine the efficacy of THC in reducing IOP for eyes with ocular hypertension and glaucoma. Clinical Trial Information: ClinicalTrials.gov Identifier: NCT02849587